Development of an Interactive E-Storybook Based on Acehnese Local Wisdom to Improve Disaster Literacy and Elementary School Students' Reading Motivation - Fatia Nurahmi; Syarfuni Syarfuni; Musdiani Musdiani (UIN Fatmawati Sukarno Bengkulu, 2026)
This study aims to develop an interactive electronic storybook based on Acehnese local wisdom and analyze its validity, practicality, and effectiveness in improving disaster literacy and reading motivation of elementary school students. The study used the Research and Development (R&D) method with the ADDIE model. The research subjects consisted of 25 fifth-grade students of Lambaro Angan Public Elementary School. The research instruments included a questionnaire, expert validation sheets, teacher and student response questionnaires, and a disaster literacy test. Data were analyzed using quantitative descriptive techniques, percentages, and N-Gain. The results showed a validity level of 96.5% with a very feasible category. Practicality based on teacher and student responses reached 100% with a very practical category. The increase in disaster literacy was seen from the average pretest score of 65.2 to 90.2 in the posttest with a high N-Gain value. The interactive electronic storybook based on Acehnese local wisdom was declared effective as a science learning medium to improve disaster literacy and reading motivation of elementary school students.